THE INFLUENCE OF PROPHET SULAIMAN'S PREACHING TO QUEEN BALQIS IN SURAH AN-NAML - Febri Wardani (Nida Al-Qur'an: Jurnal Pengkajian Islam, 2025)
Allah has explained in the letter An Naml about the story of the prophet Solomon and Queen Balqis. Queen Balqis is often used as evidence about the permissibility of a woman to become a leader and she is a woman who worships the sun. The story of Queen Balqis and the prophet Solomon is in verses 15 to 44. A person when he has power and a kingdom, will have a high ego to maintain his dignity. However, the interesting thing is about the prophet Solomon and Queen Balqis. The prophet Solomon preached to Queen Balqis which is explained in the letter and verse. How did the prophet Solomon's preaching influence Queen Balqis? The purpose of this study is to describe the influence of the prophet Solomon's preaching to Queen Balqis and to analyze the interpretation of the letter An Naml verse 44 in various interpretations using the tahlili method. The type of research in this article is library research. In this study, the researcher used interpretation as the main source of data (primary). The result of this discussion is that the preaching carried out by Prophet Solomon was to build a magnificent palace. When Prophet Solomon said to Queen Balqis, this is actually a smooth palace made of glass. Queen Balqis said, yes, my Lord, indeed I have done wrong to myself and I surrendered with Sulaiman to Allah of the universe, then he converted to Islam by recognizing that Islam is the True Religion.